El uso del paracaídas en las actividades lúdicas, como un medio para reforzar el valor de la cooperación - Monge Alvarado, María de los Ángeles (2011)
When teachers initiate playful activities with their students, they always seek to extend the game to an integral education, where human values have great relevancy. The value of cooperation is one of them and, across activities with materials like the parachute, the value is easily understood by the pupils. It is necessary to remember that Vygotski (1979) refers to the transcendence of the game as both a central factor of learning and a generator of social adjustment in the development that child undergoes in collective and social activities. Cooperative games are proposed to diminish the manifestations of aggressiveness in games that promote attitudes of sensibility, cooperation, communication and solidarity (Perez, 1998). Children play with others and not against others; they play to overcome challenges or obstacles and not to overcome others. Parachute activities are annexed which can be implemented also by materials like sheets or long fabrics, in case of difficulty getting the original material.